X-Ray flourescence (XRF) elemental composition of Euphorbia hirta Linn (Asthma weed) as a medicinal plant - Kntapo, Fatimah M; Salisu, Abubakar G; Said, Rukaiyat M (Asian Journal of Medical and Biological Research, 2018)
Euphobia hirta (Eh) was subjected to elemental analysis using X-ray fluorescence (XRF), and the results revealed the following concentrations of the elements : sulphur (4.128 mg/kg), potassium (58.755 mg/ kg), calcium (34.102mg/kg), scandium (0.256mg/kg), titanium (0.348 mg/kg), iron (2.124 mg/mg), zinc (0.108 mg/kg), rubidium (0.040 mg/kg), strontium (0.089mg/kg), zireonium (0.026mg/kg), molybdenum (0.006 mg/kg) and thorium (0.120 mg/kg) respectively. All elements analysed above were within the permissible limit set by World Health Organization (WHO) and Food and Agricultural Organization (FAO).Vanadium, chromium, manganese, cobalt, nickel, copper, arsenic, selenium, palladium, silver, cadmium, tin, antimony, tellurium, caesium, barium, tungsten, gold, mercury and lead were not detected in the sample. Asian J. Med. Biol. Res. March 2018, 4(1): 49-54